Позначка "совєтизм" у "Практичному словнику синонімів української мови" С. Караванського - Ренчка, І. (Лексикографічний бюлетень, 2015)
Мета пропонованої статті – виявити склад лексичних одиниць, позначених у «Практичному словнику синонімів української мови» С. Караванського (далі – ПССУМ-5) ремаркою «совєтизм», систематизувати їх та окреслити особливості їхнього функціонування в українській мові. This article systematizes and analyzes the lexical units marked as «sovietisms» in the «Practical dictionary of synonyms of the Ukrainian language» by S. Karavanskyi. It has been found that the scientist classifi es the sovietisms to be the lexical and morphological russianisms, words and expressions formed by calquing, orthographic norms and word stress patt erns, borrowed from the Russian language. Th e peculiarities of functioning of the sovietisms in the Ukrainian language are examined. Th e conclusion about the negative eff ects of the Russifi cation policies of the Soviet Union on the development of the Ukrainian language is made.